RESEARCH & LABORATORY INTERNSHIP IN ANDROLOGY/MALE INFERTILITY: EFFECTS OF CRYOPRESERVATION ON SPERMATIC PARAMETERS, DNA INTEGRITY AND MITOCHONDRIAL ACTIVITY - Li, Fernanda Carina Montagne (2023)
Relatório de Estágio do Mestrado em Genética Clínica Laboratorial apresentado à Faculdade de Medicina